2022
DOI: 10.17762/ijcnis.v9i3.2307
|View full text |Cite
|
Sign up to set email alerts
|

New Key Generation and Encryption Algorithms for Privacy Preservation in Mobile Ad Hoc Networks

Abstract: Mobile Ad Hoc Networks (MANETs) get widespread applications along with the evolving technologies. However, MANETs are at risk due to the shortage of security mechanisms. In this paper, we propose new algorithms for key generation and encryption for privacy preservation in MANETs. Our key generation algorithm modified Fibonacci sequence by adding scrambling factors to generate random key sequences with required length but incurred low computational overhead, whereas the encryption/decryption algorithm utilizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Our aim of this paper is to develop an authentication scheme which provides two-factor authentication and overcome the threat of a PRKG. The scheme applies an efficient cryptographic technique inspired from Amiruddin et al [9] and Verma and Jain [10] to generate multiple keys for voters which authorize them to vote and retain the authenticity of the voter. The authentication scheme supports the registration phase of an online voting system which supports medium to large scale elections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our aim of this paper is to develop an authentication scheme which provides two-factor authentication and overcome the threat of a PRKG. The scheme applies an efficient cryptographic technique inspired from Amiruddin et al [9] and Verma and Jain [10] to generate multiple keys for voters which authorize them to vote and retain the authenticity of the voter. The authentication scheme supports the registration phase of an online voting system which supports medium to large scale elections.…”
Section: Introductionmentioning
confidence: 99%
“…Amiruddin et al [9] found that key generation techniques are proposed whose performance is measured by testing the algorithm for its key generation speed, key randomness, periodicity and complexity of the algorithm. Verma and Jain [10] studied Reed Solomon codes and parity check matrices are used in correcting passwords that are entered incorrect by the user with minute error.…”
Section: Introductionmentioning
confidence: 99%